Citizenship Station Park, Teresina, Piauí, Brazil: landscape creation, implantation and temporal evolution process (Research, Society and Development, 2020)
Urban parks are places created to ease the urban life, in order to promote a more direct contact with nature, providing leisure and better quality in the way of living in cities. In this way, the general objective of this research was to analyze the process of creation and implantation, as well as to characterize the physical infrastructure, the temporal evolution of the landscape of the Station Citizenship Park Maria Socorro de Macêdo Claudino, located in Teresina, Piauí, Brazil. For this, the study was based on bibliographic, documentary and field research, and was based on the methodological aspects proposed by Sousa et al. (2017). As a result, it was found that the process of creating and implementing this Park took place between 2009 and 2016, in that time it is observed that its space has undergone several changes and the landscape has evolved from changes in the visual, physical structure and vegetal cover. It is concluded that the Citizenship Station Park is configured as a place of leisure, sports, environmental education, social interaction and cultural and religious events in Teresina city, presenting itself preserved and with efficient maintenance, which transmits to frequenters the feeling of security and harmony and, being a green space located in the “heart of Teresina", which facilitates access to other areas of the city (north, south, east and southeast), and, consequently, the increase in ecological benefits and aesthetic to its passers-by.